The ethylene/metal(0) and ethylene/metal(I) redox system: model ab initio calculations - Alex, Alexander; Hänsele, Elke; Clark, Timothy (Journal of Molecular Modeling, 2006)
Ab initio calculations ( coupled cluster with single and double excitations; CCSD) have been used to investigate the model redox systems ethylene: M( 0) ( M = Li, Na, K, Rb, Cs) and ethylene: M( I) ( M = Be, Mg, Ca, Sr, Ba, Zn, Cd, Hg). Within C-2v symmetry, the ground ((2)A(1)) states correspond to the charge distribution given in the title. The lowest (B-2(2)) excited states correspond, somewhat counter intuitively, to the ethylene (center dot-)/M(II) ion pair: These trends can be rationalized on the basis of simple electrostatic and configuration-mixing arguments that lead to two simple equations for predicting the electron-transfer energies for oxidation or reduction of the ethylene. The electron-transfer energies to the B-2(2) ion pairs are dominated by the electrostatic ion-pairing energies.
Keywords: electron transfer; ab initio; CCSD(T); ethylene